البروبرانولول والأورام الوعائية الطفلية: دراسة تجريبية عشوائية. - حسن فوز; ديب غزل; اسحق زين (Latakia University Journal -Medical Sciences Series, 2019)
Background: Hemangiomas are the most common benign vascular tumors of infancy. Although most infantile hemangiomas (IHs) have the ability to involute spontaneously after initial proliferation and resolve without consequence, intervention is required in a subset of IHs, which develop complications resulting in ulceration, bleeding, or aesthetic deformity. The primary treatment for this subset of IHs is pharmacological intervention, and propranolol has become the new first-line treatment for complicated hemangiomas. Objects: To assess propranolol efficacy and safety in complicated infantile hemangiomas in two different age groups. Patients & methods: We report on 30 infants with infantile hemangiomas, age (1-84) months, treated with oral propranolol 2 mg kg day at different ages for a period of six months. Inclusion criteria were all patients with infantile hemangioma at ages from 1 month who had had not received any previous therapy. The evolution of all hemangiomas since baseline (pre-therapy) until the end of follow-up was assessed on the basis of clinical features (color, palpable softening, and size ) and taken at follow up visits by two different physicians . Results: Our results showed that propranolol was effective in arresting the proliferative phase and in accelerating the involution of infantile hemangiomas in 93.3 % of cases. Propranolol efficacy was clear even when it was started after 12 months of life. bronchospasm was the most common side effect and was moderate to severe which indicated cessation of the treatment for three days in some case[1] Conclusion: Propranolol hydrochloride at a dose of 2 mg kg day is effective in treating infantile hemangioma. ضمت هذه الدراسة عيّنة من 30 طفلاً تراوحت أعمارهم بين شهر واحد و7 سنوات، مصابين بأورام وعائية طفلية، وتوزعوا على مجموعتين عمريتين. تمت معالجتهم بالبروبرانولول الفموي بجرعة 2 ملغ كغ اليوم لمدة ستة أشهر. معايير الاشتمال تمثلت بجميع الأطفال المصابين بالأورام الوعائية الطفلية ممن تلقوا أو لم يتلقوا علاجات سابقة. قيمت فعالية العلاج من خلال الفحص السريري للأورام (اللون, القياس, الملمس) من قبل طبيبين غير الطبيب الفاحص الأساسي, وأُخذت الصور الفوتوغرافية عند كل زيارة. وجدنا أن البروبرانولول الفموي بجرعة 2 ملغ كغ اليوم تمكن من إيقاف النمو الورمي وتسريع التراجع عند 93.3% من الحالات حتى عند الأطفال بعمر أكبر من سنة. التشنج القصبي هو أشيع الآثار الجانبية, تراوح بين متوسط وشديد اضطرنا أحياناً لإيقاف العلاج لمدة لم تتجاوز الثلاث أيام غالباً.